Integration of Team Performance, Emotional Intelligence, and Human Resource Management Practices: A Systematic Review - Anacleto Roberto Carolina Soares; Francisco Martins Da Silva; Frasto Biyanto; Miswanto, Miswanto; Wing Wahyu Winarno (International Journal of Asian Business and Management, 2024)
In this article, we will discuss how to combine team performance with emotional intelligence and use human resource management practices in an increasingly competitive globalization situation. Research data was collected through trusted journal databases such as Scopus and Google Scholar to ensure broad and relevant literature coverage. You can search for literature using Publish or Perish (POP) applications and enter keywords relevant to the research subject. In order to gain a more holistic understanding of the research subject, data collection involved combined methods using quantitative and qualitative analysis. In the current era of globalization, the level of productivity and sustainability of an organization can be improved through teams that work effectively, have good emotional intelligence skills, and implement optimal human resource management practices. The importance of this Research is highly visible in increasing understanding of the relationship between these factors and how they affect business today